Acute Care Practice in the United States: The Roles of Occupational Therapy and Physical Therapy in Early Rehabilitation - Suzanne E. Holm; Kelly Nelson; Angela Patterson (康复学报)
This review article describes the patterns and trends of early rehabilitation (ER), occupational therapy (OT) and physical therapy (PT), and the specific roles of rehabilitation therapists, particularly occupational therapists (OTs) and physical therapists (PTs) in acute care hospitals in the United States (U. S.). First, a broad overview of the research literature related to the consequences of bed rest and immobility is presented along with the techniques used by OTs and PTs to minimize negative outcomes and optimize function through ER. Occupation-based and mobility-focused practices are then outlined to describe rehabilitation therapy's role in decreasing readmissions and improving patient and family satisfaction. Finally, traditional OT and PT practices in acute care settings in China, including the challenges of implementing ER and the implications for contemporary practice, are discussed. ER refers to the initiation of therapy services in an expedited manner for patients who have rehabilitative, safety, or community support needs in the acute care hospital. That is, after experiencing an injury, illness, or disease, patients'occupational performance and ability to participate in activities and mobility can be improved, or prevented from worsening, with ER. The goals of OT and PT in an accelerated and fast-past hospital environment are to facilitate a patient's functional performance and outcomes to improve function recovery and to prevent further disability and loss of function. Currently in U. S., federal regulations, health care policies, financial constraints, and the demanded shortened hospital stays require therapists to be both comprehensive and efficient and to continue advancing ER practices. Early rehabilitation must be well-timed and intensive enough to bring about positive changes. Additionally, ensuring patients'active engagement and addressing therapy goals that patients and families identified as essential are imperative to achieve patients'successful transition to home or to another setting. Through ER, not only can a patient's functional abilities improve, but ER reduces the risk of undesirable and unintended health consequences. Such hospital-acquired conditions (HAC) are conditions which occur during a patient's hospitalization and are not present at admission. The risk of developing HAC increases if the patient is limited from active engagement in activity and mobility as a result of bed rest, immobility, or deconditioning. Systemic deconditioning, which can result from a prolonged critical illness, a trauma, or a surgery, reduces the patient's functional capacity, impairs cognitive abilities, diminishes psychological coping, and increases rates of depression and anxiety. With ER, the specific OT and PT rehabilitative interventions minimize the risk for negative health conditions, impairments, and disability while simultaneously promoting functional recovery. Specific to each rehabilitation profession's roles and responsibilities in the U. S., OTs promote the patients'occupational performance and participation in daily occupations, roles, habits, and routines. Through facilitating the patient's engagement in typical activities of daily living, OT improves patient's overall health, well-being, and independence at home and in the community. In addition to direct therapy service to patients, OTs also assess and recommend specific task and environmental modifications. Occupational therapists'intervention may focus on compensatory (i.e., facilitating occupation through modifying the task or environment) or remediation (i.e., rehabilitative) techniques for patients to achieve a greater level of independence. In PT, the emphasis is on promoting and progressing patients'mobility and movement to increase performance and to enhance function, well-being, overall health and quality of life. PTs promote optimal mobility to enable patients to achieve a greater level of independence, autonomy, and to return to previous or enhanced level of function. Any patient who has or may develop impairments, activity limitations, and participation restrictions related to musculoskeletal, neuromuscular, cardiovascular, pulmonary, and integumentary systems can be treated by PT. Therefore, PTs are well-suited to promote early rehabilitation (ER) in the acute care setting. In the U. S., currently, however, acute care hospitals are not often designed to support patients and meet their intensive rehabilitation needs. Consequently, patients who require assistance with daily occupations or mobility or who have ongoing rehabilitation needs often result in relocating, or transferring to another health care facility, i.e., post-acute care, for continued recovery of medical issues and rehabilitative deficits. Multiple levels of post-acute care are available in the U. S.including skilled nursing facilities, rehabilitation hospitals, long-term acute care hospitals, nursing homes, outpatient clinics, home health, and private caregiver services. Currently, in the Chinese acute care hospital, patients have the option to stay for an extended period of time which provides the opportunity for OTs and PTs to provide multiple rehabilitation visits. Typically, the outcomes of OT and PT services are to restore physical mobility, increase active range of motion, and improve function in order for the patient to return home with family. It seems, due to the Chinese culture, tradition and custom, less emphasis is on improving independence with self-care activities. It is expected that family members take on the responsibilities to provide care to a family member who is ill or has disabilities. As such, in China there is typically a supportive family dynamic, meaning the family is present daily during rehabilitative intervention, helping provide therapeutic exercises and physical agent modalities for their loved ones. The burden of care on the family members worsens at discharge, especially if the patient and family have not received therapy or patient education to improve the patient's function and independence. Currently, the profession of rehabilitation including occupational therapy and physical therapy in China is in an excellent position of growth and advancement. Understanding the unique roles of OT and PT in acute care from an international perspective will improve global health not only through rehabilitative services, but also through focusing on health and wellness for the patient, family, and community. Early rehabilitation in the acute care setting is an effective way to improve the health and well-being of patients and enable them to return to their home and community in a timely manner. OTs and PTs play instrumental roles in early rehabilitation in the acute care settings.